Cotton GhBAK1 Mediates Verticillium Wilt Resistance and Cell Death1. Issue 7 (18th July 2013) - Gao, Xiquan; Li, Fangjun; Li, Maoying; Kianinejad, Ali S.; Dever, Jane K.; Wheeler, Terry A.; Li, Zhaohu; He, Ping; Shan, Libo
Abstract: Virus‐induced gene silencing (VIGS) offers a powerful approach for functional analysis of individual genes by knocking down their expression. We have adopted this approach to dissect gene functions in cotton resistant to Verticillium wilt, one of the most devastating diseases worldwide. We showed here that highly efficient VIGS was obtained in a cotton breeding line (CA4002) with partial resistance to Verticillium wilt, and GhMKK2 and GhVe1 are required for its resistance to Verticillium wilt. Arabidopsis AtBAK1/SERK3, a central regulator in plant disease resistance, belongs to a subfamily of somatic embryogenesis receptor kinases (SERKs) with five members, AtSERK1 to AtSERK5. Two BAK1 orthologs and one SERK1 ortholog were identified in the cotton genome. Importantly, GhBAK1 is required for CA4002 resistance to Verticillium wilt. Surprisingly, silencing of GhBAK1 is sufficient to trigger cell death accompanied with production of reactive oxygen species in cotton. This result is distinct from Arabidopsis in which AtBAK1 and AtSERK4 play redundant functions in cell death control. Apparently, cotton has only evolved SERK1 and BAK1 whereas AtSERK4/5 are newly evolved genes in Arabidopsis . Our studies indicate the functional importance of BAK1 in Verticillium wilt resistance and suggest the dynamic evolution of SERK family members in different plant species.